Structural-functional and parametric analysis of the social function of pharmaceutical industry - N. O. Tkachenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2016)
Pharmacy has always had a special (social) value and was sensitive to the new social changes in the society and the state. These changes allow better understand the issues associated with increasing the efficiency of pharmaceutical care to the population.